Multimorbidity in Hospitalized Patients Admitted to General Practice Departments and Its Implications for the General Practice Healthcare System: A Four-Year Longitudinal Study in China - Zhou, Zhihan; Shi, Meng; Liu, Mengzhu; Gu, Jianqin; Silver Tarimo, Clifford; Wu, Jian; Miao, Yudong (Frontiers in Public Health, 2021)
Objective: China and many developing countries has placed high expectations on the general practice healthcare system in terms of lowering medical costs and improving the health status of the multimorbid population in recent years. However, the prevalence of multimorbidity among inpatients attending the general practice department of hospitals and its policy implications are largely unknown. The current study aimed to analyze the prevalence of comorbidities among inpatients attending the general practice department of the tertiary Grade-A Hospitals in China, and put forward evidence-based policy recommendations. Methods: Between December 2016 and November 2020, 351 registered general practitioners from 27 tertiary hospitals were selected, and their direct admissions were evaluated. The rate and composition ratio were used for descriptive analysis of the clinical and epidemiological characteristics of multimorbidity. A backward stepwise algorithm was used to explore independent variables. The absence of multicollinearity and plausible interactions among variables were tested to ensure the robustness of the logistic regression model. The pyramid diagram was used to show the link between gender and the involved human body system in multimorbidity. Results: Multimorbidity was present in 93.1 percent of the 64, 395 patients who were admitted directly. Multimorbidity was significantly more prevalent in patients aged 45-59 years (OR=3.018, 95% CI=1.945-4.683), 60-74 years (OR=4.349, 95% CI=2.574-7.349), ≥75 years (OR=7.804, 95% CI=3.665-16.616), and those with body mass index (BMI) ≥28 kg/m2 (OR=3.770, 95% CI =1.453-9.785). The circulatory system was found to be the most commonly involved human body system in multimorbidity, accounting for 79.2% (95% CI=78.8%-79.5% ) of all cases. Significant gender inequity was further observed in the involved human body system in multimorbidity. Conclusion: Multimorbidity is likely common among the inpatients attending the general practice department of hospitals in China and many developing countries, with significant gender inequity in the involved human body systems. Effective countermeasures include establishing a GP-PCIC multimorbidity prevention and control model and enhancing the multimorbidity of elderly and obese patients at both the clinical and healthy lifestyle levels. The diagnosis and treatment capabilities of GPs on the circulatory, endocrine, metabolic, digestive, and respiratory systems should be prioritized.